2011
DOI: 10.1186/1471-2156-12-77
|View full text |Cite
|
Sign up to set email alerts
|

The impact of modern migrations on present-day multi-ethnic Argentina as recorded on the mitochondrial DNA genome

Abstract: BackgroundThe genetic background of Argentineans is a mosaic of different continental ancestries. From colonial to present times, the genetic contribution of Europeans and sub-Saharan Africans has superposed to or replaced the indigenous genetic 'stratum'. A sample of 384 individuals representing different Argentinean provinces was collected and genotyped for the first and the second mitochondrial DNA (mtDNA) hypervariable regions, and selectively genotyped for mtDNA SNPs. This data was analyzed together with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
44
2
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 59 publications
9
44
2
7
Order By: Relevance
“…These results for D1g and D1j are concordant with a recent study (Bobillo et al 2010), in which the lineage here termed ''D1g'' was found at an overall frequency of 4.73% in Argentina (almost exclusively in the south, at a local high of 27.7%) and the lineage now termed ''D1j'' at 2.66%. These figures differ only slightly from the ones in another recent report (Catelli et al 2011), in which the frequency of D1g in Argentina was 1.3% and that of D1j 3.9%. For details on database frequencies, see Supplemental Table S4.…”
Section: Frequency Patterns Of D1g and D1jcontrasting
confidence: 88%
See 2 more Smart Citations
“…These results for D1g and D1j are concordant with a recent study (Bobillo et al 2010), in which the lineage here termed ''D1g'' was found at an overall frequency of 4.73% in Argentina (almost exclusively in the south, at a local high of 27.7%) and the lineage now termed ''D1j'' at 2.66%. These figures differ only slightly from the ones in another recent report (Catelli et al 2011), in which the frequency of D1g in Argentina was 1.3% and that of D1j 3.9%. For details on database frequencies, see Supplemental Table S4.…”
Section: Frequency Patterns Of D1g and D1jcontrasting
confidence: 88%
“…To better evaluate the geographical distribution of the novel haplogroups, we surveyed published and unpublished CR data from a wide range of populations (Ginther et al 1993;Horai et al 1993;Alves-Silva et al 2000;Moraga et al 2000;Lalueza-Fox et al 2001;García-Bour et al 2004;Tajima et al 2004;Cabana et al 2006;Á lvarez-Iglesias et al 2007;Tamm et al 2007;Carvalho et al 2008;Salas et al 2008;Bobillo et al 2010;Catelli et al 2011;Gayà-Vidal et al 2011;Prieto et al 2011;Sans et al 2011;MC Bobillo, unpubl.). This allowed the identification of 103 putative D1g and D1j mtDNAs (Supplemental Table S3).…”
Section: Phylogeographic Patterns Of D1g and D1jmentioning
confidence: 99%
See 1 more Smart Citation
“…Research using data from modern populations is complicated by the fact that, although some populations (e.g. that of Venezuela) reveal relatively high frequencies of indigenous haplogroups, many indigenous South American populations have been impacted by significant inflows of European and African genes over the last 500 years (Salas et al 2004, Mendizabal et al 2008, Catelli et al 2011, Gómez-Carballa et al 2012). …”
Section: Peopling Of South Americamentioning
confidence: 99%
“…A Maximum Likelihood (ML) estimate of Gamma parameter for Site Rates (Gamma distribution), was used to model evolutionary rate differences among sites (5 categories, [+G]: AC=AT=CG=GT, AG=CT) and to estimate nucleotide frequencies. The problem variation located around nucleotide position 16189 is usually associated with the length of heteroplasmy (Catelli, et al 2011); therefore the 16182 and 16183 positions (B2 haplogroup) were ignored to calculate diversity indices, genetic distances, NJ phylogeny, and rates/patterns of nucleotide substitution for the Checua group. (5) (Kirkman 1996, Soper 2015.…”
Section: Methodsmentioning
confidence: 99%